Sierra Leone : Poverty Reduction Strategy Paper; Annual Progress Report. (IMF Staff Country Reports; Country Report, 2007)
This report describes the progress made in implementing the Poverty Reduction Strategy Paper (PRSP) for Sierra Leone from June 2005 to May 2006. The improvement in the external sector has for the most part reflected a strong improvement in export performance, particularly for diamonds. Efficient aid and public debt management policies have significantly improved donor confidence and development assistance. Structural reforms have helped to establish a basis for sound public finances and the effective conduct of macroeconomic policies. The economic outlook in the medium-term continues to improve.